Synthesis, characterization and influence of pH on indium doped zinc oxide nanostructures. Issue 18 (15th December 2019) - Seid, Endris Taju; Dejene, Francis B.; Kroon, R.E.
Abstract: Indium doped zinc oxide (In:ZnO) nanostructures were synthesized using the refluxed sol-gel method at pH levels of 7, 8, 9, 10, 11 and 12 for the precursor solution, adjusted by the addition of aqueous sodium hydroxide to the solution mixture of zinc and indium salts. X-ray diffraction (XRD) patterns revealed intense diffraction peaks of wurtizite In:ZnO nanocrystals with increased broadenings due to the incorporation of larger size In 3+ ions to the lattice sites of Zn 2+ ions. The substitution process of the dopant ions into the lattice sites and the size of the crystallites were influenced and facilitated by the pH of the solution. The crystallite size decreased from 23 nm to 19 nm with an increase of pH level of the precursor solution. The micrograph from field emission scanning electron microscopy (FE-SEM) showed an aggregated mixture of spindle- and cone-like morphology which decreased in size as the solution pH increased. Transmission electron microscopy (TEM) also confirmed the morphology and the decrease in size of the structures obtained by FE-SEM measurements. The UV–Vis reflectance analysis also demonstrated that the optical properties of In:ZnO crystallites improved with the increase in pH of the solution, as shown by the blue shift of the absorption edge of the reflectance spectra. The energy band gap increased nearly linearly from 3.22 eV to 3.26 eV with the increased pH values from 7 to 12 which was attributed to the Burstein-Moss effect. Photoluminescence (PL) measurements show a significant change in the emission characteristics. Both excitonic and defect level emission bands were shifted to shorter wavelength as the pH level increased, verifying the widening of the energy band gap. The relative intensity ratios of excitonic to defect level emission bands ( I NBE /I DLE ) decreased generally as the pH level increased, indicating the increased concentration of the defects of oxygen interstitials and vacancies in the produced nanostructures. All measurements exhibited in this study confirmed that increasing the alkalinity of the synthesis solution enhanced the production of highly crystalline In-doped ZnO nanostructures for a better and suitable material in the area of biomedical, solar cell and other optoelectronics applications.